Materials of the 3nd All-Russian Conference on Molecular Oncology Moscow, 6–8 December 2017 - Article Editorial (Успехи молекулярной онкологии)
Materials of the 3nd All-Russian Conference on Molecular Oncology Moscow, 6–8 December 2017.